Isolation of Keratin from Waste Wool Using Hydrothermal Processes - Aleksandra Verdnik; Maja Čolnik; Željko Knez; Mojca Škerget (Acta Chimica Slovenica, 2021)
The subcritical water (SubCW) extractions of waste wool to produce keratin were performed at temperatures of 150 °C to 250 °C and at different reaction times between 5 min to 75 min. The resulting proteins in the obtained products were confirmed with Fourier-transform infrared spectroscopy (FTIR). The molecular weight of the protein extracts was determined by using two different methods: with a polyacrylamide gel electrophoresis in the presence of sodium dodecyl sulphate (SDS-PAGE) and by using a gel permeation chromatography. The results show, that by using SubCW, keratin can be isolated from waste wool in very high yields, much higher than by other chemical methods. Maximal yield was achieved at 180 °C and 60 min and it was 90.3%. The molecular weight distributions of extracted proteins, which were generated from waste wool were between 14 kDa and 4 kDa, what is comparable to the results obtained by other chemical methods.